Magnetically coupled quantum-flux-latch with wide operation margins. (29th September 2015) - Tsuji, Naoki; Takeuchi, Naoki; Narama, Tatsuya; Ortlepp, Thomas; Yamanashi, Yuki; Yoshikawa, Nobuyuki
Abstract: We have been developing adiabatic quantum-flux-parametron (AQFP) circuits as an ultra-low-power superconductor logic for energy-efficient computing. In a previous study, we proposed and demonstrated a quantum-flux-latch (QFL), which is a compact and compatible latch for AQFP logic. The QFL is composed of an AQFP buffer gate and a storage loop, which are directly connected to each other. However, the operation margins were not sufficiently wide due to a trade-off between the operation margins of the storage loop and that of the buffer gate. In this present study, we propose a magnetically coupled QFL (MC-QFL), where the storage loop and the buffer gate are physically separated and magnetically coupled to each other to eliminate the trade-off in the operation margins. The simulation results showed that the critical parameter margin of the MC-QFL is twice as large as that of the previously designed QFL. For comparison, we fabricated and demonstrated both the previously designed QFL and the newly designed MC-QFL. The measurement results showed that the MC-QFL has wider operation margins compared with the previously designed QFL.